Recreational leadership and business ethics: a study on animation staff - Demirdağ, Şerif Ahmet; Güçer, Evren (Afyon Kocatepe Üniversitesi)
The human factor in each service business has a very important position in effectiveness, efficiency and achieving goals of establishments. The animation department in the hotels plays also very important role so as to influence the decision-making process of customers and their loyalty to hotels. However, the animation staff working in this department should work in accordance with business ethics and morale as they are in close contact with the consumer. Furthermore, the animation staff can be considered as a “recreational leader” which leads to the recreational activities in hotels. The aim of this research is to determine the relationship between recreational leadership attitudes and views of business ethics of the animation staff. For this purpose, the data is collected by questionnaire which applied on 580 animateurs working in 65 resort hotels in Antalya, Muğla and Aydın. According to results of analysis, there was a significant relationship between recreational leadership attitude and business ethics of participants.

Her hizmet sektöründeki insan faktörü, işletmelerin etkinlik, verimlilik ve hedeflerine ulaşma konusunda çok önemli bir konuma sahiptir. Otellerdeki animasyon departmanı da müşterilerin karar alma süreçlerini ve otellere olan bağlılıklarını etkilemede oldukça önemli bir rol oynamaktadır. Bununla birlikte, bu bölümde çalışan animasyon personeli, tüketici ile yakın temas halinde oldukları için iş etiği ve ahlakına uygun olarak çalışmalıdır. Bununla birlikte, animasyon personeli otellerde rekreasyon faaliyetlerine öncülük eden “rekreasyon liderleri” olarak kabul edilmektedir. Bu araştırmanın amacı, animasyon personelinin rekreasyon liderlik tutumları ile iş etiği görüşleri arasındaki ilişkiyi belirlemektir. Bu amaç doğrultusunda araştırma verileri, Antalya, Muğla ve Aydın'da faaliyet gösteren 65 otelde çalışan toplam 580 animatöre uygulanan anket formu ile toplanmıştır. Analiz sonuçlarına göre, katılımcıların rekreasyon liderlik tutumları ile iş etiği görüşleri arasında anlamlı bir ilişki tespit edilmiştir.
Rekreasyonel liderlik ve iş etiği: animasyon personeli üzerine bir araştırma
Keywords: Recreational leadership; Business ethics; Animation; Hotels